Living condition in the low cost apartments in Malaysia: an empirical investigation - Karim, A.H.M Zehadul (Canadian Center of Science and Education, 2013)
This research on low-cost housing is a detailed socio-cultural background of the people living in the apartment-housing in Malaysian context. Purposefully, this research has been done to explore the housing situation in two low-cost apartments located in Gombak, Kuala Lumpur having based on a sample survey of 60 households who were interviewed and investigated most extensively to know the prevailing cultural fabrics and living condition in these two selected apartment houses. Because there is a fast pace of urban development in Malaysia, it therefore becomes a vital issue for us to understand what is happening in the life of this group of people who have had settled in these low-cost apartments. Based on our objectives, this paper deals with the dwelling features and living condition of the people housed in these low-cost apartments and accordingly, generates data on the basic amenities of life of the people residing in these low cost accommodations. On the basis of our findings, the research finally provides some suggestions in the form of specific recommendations for future planning.